A new generation of predictive models: The added value of hybrid models for manufacturing processes of therapeutic proteins. Issue 10 (21st July 2019) - Narayanan, Harini; Sokolov, Michael; Morbidelli, Massimo; Butté, Alessandro
Abstract: Due to the lack of complete understanding of metabolic networks and reaction pathways, establishing a universal mechanistic model for mammalian cell culture processes remains a challenge. Contrarily, data‐driven approaches for modeling these processes lack extrapolation capabilities. Hybrid modeling is a technique that exploits the synergy between the two modeling methods. Although mammalian cell cultures are among the most relevant processes in biotechnology and indeed looks ideal for hybrid modeling, their application has only been proposed but never developed in the literature. This study provides a quantitative assessment of the improvement brought by hybrid models with respect to the state‐of‐the‐art statistical predictive models in the context of therapeutic protein production. This is illustrated using a dataset obtained from a 3.5 L fed‐batch experiment. With the goal to robustly define the process design space, hybrid models reveal a superior capability to predict the time evolution of different process variables using only the initial and process conditions in comparison to the statistical models. Hybrid models not only feature more accurate prediction results but also demonstrate better robustness and extrapolation capabilities. For the future application, this study highlights the added value of hybrid modeling for model‐based process optimization and design of experiments. Abstract : Both mechanistic and data‐driven modeling approaches for bioprocesses have advantages and disadvantages. Hybrid modeling is a new generation of predictive tool that combines the strength of both these modeling approaches to provide a robust and accurate tool suitable for process design and optimization and for digital twin based applications.